Means of designing object-oriented programs based on algebra of algorithmics - Doroshenko, А.Yu.; Iovchev, V.A. (PROBLEMS IN PROGRAMMING, 2015)
Means for representation of sequential and parallel programs based on algorithmic description reviewed. Methods for dialog design and synthesis of parallel and object-oriented programs in Java described. Instrumental toolkit based on aforementioned methodology presented.